Repetitive sprint ability in elite ice hockey players - Tschopp, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: The repetitive sprint ability (RSA) is an important physical factor for ice hockey players (Noonan, 2010). However, there exists no validated test analyzing RSA in ice hockey players that mimics the actual work to recovery ratio of the game. The aim of the present study was twofold: 1) to explore whether an on-ice repetitive sprint test with a hockey-specific work to recovery ratio is able to discriminate between hockey players of different performance levels; and 2) to evaluate the relationship between the hockey-specific RSA, and aerobic and anaerobic fitness. Methods: 12 professional elite ice hockey players (PROF; 25.4± 2.4 J.; 90.1 ± 5.9 kg; 184.6 ± 4.1cm), and 15 non-professional elite ice hockey players (NPROF; 23.9±4.4J.; 84.4±8.5kg; 181.1±5.5cm) completed a repetitive shuttle sprint test (RISS) with full equipment on ice. The test includes 3 series of 4 all-out sprints with a 180° turn (2x15m). Every 20 seconds, the players would begin the next sprint. Between the series, there was a passive recovery period of 3 minutes. Within 3-7 days after the RISS the participants performed a VO2max-test on a cycle ergometer, a Wingate-Test (WINGATE) and a jump test on a force plate (JUMP) in the laboratory. For statistical analysis, Cohen`s effect size (ES), unpaired t-Test and Pearson`s correlation coefficient were used (p <0.05, *). Results: Significant differences between PROF and N-PROF were found for total sprint time (PROF 43.98±1.19 vs. N-PROF 44.99±1.08sec; ES 0.89, p=0.03), and for the sprint time of the second (ES 1.09, p=0.01) and third RISS series (ES 0.78, p=0.05). No relevant difference was found for the best RISS sprint time (3.40±0.11 vs. 3.43±0.10sec, ES 0.29). Only moderate to small ES were obtained in the laboratory tests with the smallest difference between PROF and N-PROF in VO2max (57.8±4.2 vs. 56.7±6.4ml/kg/min; ES 0.21; WINGATE Mean Power: ES 0.66; JUMP Peak Power: ES 0.73). Total RISS sprint time moderately correlated with WINGATE Mean Power (r=0.54*) and JUMP Peak Power (r=0.55*). VO2max significantly correlated with the decrement of the sprint time between series (r= - 0.50*) but not with RISS total sprint time (r=0.38). Discussion: The RSA measured with a repeated shuttle sprint test on-ice with a hockey-specific work to recovery ratio is able to discriminate between ice hockey players of different performance levels to a greater extent than a single shuttle sprint or classic laboratory fitness tests. The hockey-specific RSA shows associations with anaerobic performance and anaerobic capacity. VO2max seems to have its importance in the ability to recover between series